Using Spatial Statistics to Examine the Pattern of Urban Land Development in Halifax-Dartmouth. - Culthbert, Angela L.; Anderson, William P. (Professional Geographer, 2002)
A study was conducted to investigate the locational patterns of population and employment and the changes in urban form that this has created in the Halifax-Dartmouth region of Canada between 1970 and 1996. Findings revealed that residential land parcels cluster together, that commercial land parcels cluster together, and that residential and commercial land parcels have become more clustered over time.